The criminalisation of poverty: social and penitentiary policy intertwined - Beszterda, Zofia (Przegląd Krytyczny, 2025)
The primary aim of this work consists of a critical analysis of the mechanisms through which conditional and employment-oriented social policy (workfare) and the expansion of the repressive functions of penal institutions (prisonfare) have laid the groundwork for phenomena that harm structurally marginalised communities and entrench existing inequalities – namely, mass incarceration and the criminalisation of poverty. Using the United States as a case study, where these phenomena have reached unprecedented levels, I analyse how economic deregulation, the abandonment of the welfare state model, and the expansion of market logic have consolidated structural mechanisms that penalise poverty. This article reflects an attempt at a sociologically engaged critique of a cycle of systemic violence, the victims of which predominantly constitute the poor, especially communities of colour.